Research Progress on Extraction Techniques and Functional Activities of Jasmine Essential Oil - Ziyang WU; Huiling WENG; Weiming LI; Liping XU; Baodong ZHENG; Xianliang LUO (Shipin gongye ke-ji)
Jasmine is a widely distributed and historically cultivated plant in China, known for its dual use as both a medicinal and culinary flower. Jasmine essential oil, extracted from the flowers, contains over 100 volatile compounds such as benzyl acetate, linalool, methyl anthranilate, and jasmone. In recent years, emerging technologies like subcritical fluid extraction and ultrasound-assisted extraction have been extensively applied to the extraction of jasmine essential oil, with the composition and yield of the oil being significantly influenced by the extraction conditions. Moreover, excellent antioxidant, antibacterial, anti-inflammatory, anti-aging, antiviral, and anticancer activities are exhibited by jasmine essential oil, making it a potential active ingredient in the fields of food, cosmetics, and pharmaceuticals. A systematic review of the chemical constituents, extraction processes, and functional activities of jasmine essential oil is provided in this article, with the aim of providing theoretical support for the potential of jasmine essential oil in the development and application of new products.